Sensation seeking and risk taking behavior of mountain climbers in Malaysia - Anuar, Siti Nursyadiq (2014)
The thrill of adventure has attracted many people to the sport of mountain climbing. The search for sensation has caused many people to launch expeditions to conquer mountains. However, they often did not consider their own safety. As a result, many have been lost in the mountains of Malaysia. Studies showed that the total number of incidents reported during mountain climbing is 56 cases in 10 years. Accidents occur not because people are not aware or do not take any precautions. The trait of sensation seeking is a possible justification for this behaviour. The objectives of the study are to determine the sensation seeking tendency of the mountain climbers, to analyze the differences in sensation seeking between gender and to examinewhether a relationship exist between sensation seeking and risk taking behaviour of the mountain climbers.The non-random sampling technique was used combining the purposive and snowball sampling technique. The questionnaire comprises 4 sections of questions were distributed during January to June 2012. The Sensation Seeking Scale comprises 35 pairs of choices of subjects that the respondents were asked to choose which of the two statement best describes their interests and preferences. While the Risk Taking Behaviour Scale measured the likelihood with which respondents might engage in risky behaviour originating from five domains of life. The results show that the mountain climbers in Malaysia were high in Sensation Seeking. They score higher in Thrill and Adventure Seeking, moderately high in Experience Seeking and Boredom Susceptibility and lower in Disinhibition. Male mountain climbers’ have higher tendencies in Thrill and Adventure Seeking, Experience Seeking and Disinhibition compare to female, while in Boredom Susceptibility, female are likely to have more tendencies. Only the trait of Thrill and Adventure Seeking and Boredom Susceptibility are significantly depending on gender. It shows that Sensation Seeking positively correlate with risk taking behaviour The influences of the environment and culture could be the reason for Disinhibition sub-trait being low in Malaysian mountain climbers. It can be said that males show greater amount of traits attributes as such aggression, neurotise, emotional stability and desire for participating in physical activities compared to female. The elements in the Sensation Seeking relates to the physical type of risk.It shows that sensation seeking is one of the personality traits that are highly correlated with the risk taking behaviour. The personality traits are the predictable ways to explain the expectation of the adventure tourism consumer that occurs differently among them.This can maximize the experience of the mountain climber so that a higher quality of experience can be achieved. The tourism marketers can also create and promote products that cater to the needs and interest of their high or low sensation seeker rather than creating or promoting products that appeal to everyone.